Stranger Harassment (“Piropo”) and Women’s Self-Objectification: The Role of Anger, Happiness, and Empowerment - Moya-Garófano, Alba (Journal of interpersonal violence, 2021)
According to objectification theory, women’s habitual exposure to sexually objectifying situations can lead them to internalize a third-person perspective of themselves in physical terms, leading women to adopt an observer’s viewpoint of themselves as a body or collection of body parts that is valued principally for use or consumption by others (i.e., self-objectification). The frequency and/or intensity of situations of female objectification have generally been studied as precedents of self-objectification. Our research analyzes whether direct exposure to a particular objectifying situation, as in the case of verbal stranger harassment (called piropos in Spain), could have these same effects. We tested the consequences of exposure to piropos (vs. a control situation) on body surveillance and body shame in a sample of 329 Spanish women. The impact of verbal harassment on women’s anger, anxiety, happiness, and sense of empowerment was also analyzed. The results of a moderated mediation analysis showed that exposure to piropos increased body shame through body surveillance but only in women who reacted to the piropo with happiness, empowerment, or low levels of anger. The negative effects that objectifying situations (e.g., stranger harassment) may have on women, and the importance of women’s reactions and perceptions of such situations are discussed.